Humanitarian intervention: its concept and historical development - Suad Abdulkadhim abdulhaeed alsaadi , Rese.; Gholamali Ghasemi , Prof. Dr. (lark, 2025)
Humanitarian intervention is a longstanding phenomenon in international relations and has gone through stages of development that helped its formation and solidification. Before the First World War, when the use of force was the main characteristic, the delegation began, subsequently, in the League of Nations era, the intervention was limited to the scope of protecting the rights of minorities. However, international practices related to intervention have increased after the Second World War and the establishment of the modern international system and the founding of the United Nations, which stipulated in its charter the necessity of protecting human rights and confronting serious violations that constitute a threat to international peace and security. However, the opinions of jurists and legal experts differ regarding the concept of intervention and its limits. Some limit it to military force, while others see it as broader, including diplomatic and economic means and political pressures. To attain world peace and security, as well as to stop serious violations it was required to explain the idea of humanitarian intervention and its historical development .